Examining the Utility and Performance of Online Scoring Rubrics in the Context of Educational Assessment (Conference on English Language Teaching, 2023)
This article examines the application and efficacy of online scoring rubrics within educational assessment. Online scoring rubrics offer several advantages over paper-based methods, including increased efficiency, consistency, and usability. The article investigates the features and functionalities of online scoring rubric systems, emphasizing their capacity to provide precise evaluation criteria, expedite the grading process, and facilitate feedback delivery. In addition, it examines the impact of online scoring rubrics on both instructors and students, considering factors such as time savings, enhanced feedback quality, and improved comprehension of assessment expectations. The article also discusses potential challenges and limitations related to adopting online scoring rubrics, such as technical issues and the need for appropriate training and support. The article concludes by discussing the benefits of using online scoring rubrics and recommendations for their effective implementation in educational contexts, drawing on existing research and practical examples.